Maternal determinants of stunting: findings from a cross-sectional study in Padang, Indonesia - Yulika, Marzatia; Syah, Nur Afrainin; Yusrawati, Yusrawati (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to investigate the influence of maternal factors on stunting in young children aged 24-59 months. Methods: This analytical cross-sectional study was conducted in a subdistrict of Padang. The dependent variable was stunting, and the independent variables were maternal factors. The sample number was 155, and it was collected using stratified and consecutive sampling techniques. Chi-square and logistic regression were applied in data analysis. Results: The study reveals no significant difference between stunted and non-stunted under-five children in terms of the following maternal factors: age at pregnancy, body mass index (BMI), gestational age, upper arm circumference, height, and education. However, both groups showed a significant difference in terms of the number of children (p = 0.041), parenting style (p = 0.006), and knowledge (p = 0.039). Logistic regression analysis showed that mothers who had poor parenting styles had a 3.186 times higher risk of having children with stunting compared to mothers who had good parenting styles (95% CI: 1.382-7.348). Conclusion: The mother's parenting style was the most influential factor in the incidence of stunting among children in Padang City. More effective preventive and intervention measures to overcome the problem of stunting need to pay attention to maternal parenting style, knowledge, and the number of children.